CCR2 contributes to host defense against Staphylococcus aureus orthopedic implant‐associated infections in mice. Issue 2 (29th March 2021) - Wang, Yu; Dikeman, Dustin; Zhang, Jeffrey; Ackerman, Nicole; Kim, Sophia; Alphonse, Martin P.; Ortines, Roger V.; Liu, Haiyun; Joyce, Daniel P.; Dillen, Carly A.; Thompson, John M.; Thomas, Abigail A.; et al.
Abstract: C‐C motif chemokine receptor 2 (CCR2) is an important mediator of myeloid cell chemotaxis during inflammation and infection. Myeloid cells such as monocytes, macrophages, and neutrophils contribute to host defense during orthopedic implant‐associated infections (OIAI), but whether CCR2‐mediated chemotaxis is involved remains unclear. Therefore, a Staphylococcus aureus OIAI model was performed by surgically placing an orthopedic‐grade titanium implant and inoculating a bioluminescent S. aureus strain in knee joints of wildtype (wt) and CCR2‐deficient mice. In vivo bioluminescent signals significantly increased in CCR2‐deficient mice compared with wt mice at later time points (Days 14–28), which was confirmed with ex vivo colony‐forming unit enumeration. S. aureus γ‐hemolysin utilizes CCR2 to induce host cell lysis. However, there were no differences in bacterial burden when the OIAI model was performed with a parental versus a mutant γ‐hemolysin‐deficient S. aureus strain, indicating that the protection was mediated by the host cell function of CCR2 rather than γ‐hemolysin virulence. Although CCR2‐deficient and wt mice had similar cellular infiltrates in the infected joint tissue, CCR2‐deficient mice had reduced myeloid cells and γδ T cells in the draining lymph nodes. Taken together, CCR2 contributed to host defense at later time points during an OIAI by increasing immune cell infiltrates in the draining lymph nodes, which likely contained the infection and prevented invasive spread.